Reliability and validity of the Arabic version of cluster headache impact questionnaire in both active episodic and chronic cluster headache - Mona Hussein; Mona AF Nada; Amr Hassan; Mohamed Abdelghaffar; Mona Ali; Alaa Elmazny; Rehab Magdy (The Journal of Headache and Pain)
Abstract Background Clinical evaluation of cluster headache (CH) impact on patients’ quality of life is crucial in research and clinical practice. To our knowledge, none of the measures that evaluated CH-related disability were validated in Arabic. This study aimed to evaluate the reliability and validity of the Arabic version of Cluster Headache Impact Questionnaire (CHIQ) in both active episodic CH (eCH) and chronic CH (cCH). Methods Patients with active eCH or cCH were requested to answer the Arabic version of CHIQ, Depression, anxiety and stress scale– 12 (DASS-12), and Short form-12 health survey (SF-12). Cronbach’s α and intraclass correlation coefficient (ICC) were used to assess the test reliability. Convergent validity and Explanatory factor analysis of CHIQ items were also assessed. Results Seventy-two patients with active eCH and another 16 with cCH were evaluated. Patients with cCH had a significantly higher median value of CHIQ total score in comparison to those with eCH (P-value < 0.001). No ceiling or floor effects were detected in CHIQ total score. The Arabic version of CHIQ showed excellent reliability (Cronbach’s α = 0.901). The intraclass correlation coefficient of CHIQ total score was 0.983 indicating excellent test re-test reliability. The CHIQ scores were significantly correlated with scores of DASS-12 (r = 0.477) and SF-12 (r=-0.691), supporting the convergent validity of the scale. Exploratory factor analysis revealed two factors labelled as “physical and cognitive impact” and “psychological impact” factors. Conclusion Arabic version CHIQ is a reliable and valid tool for measuring CH-related disability and quality of life in patients with eCH and cCH.